2017
DOI: 10.4142/jvs.2017.18.4.419
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of resveratrol on hepatitis B virus X protein-induced hepatocellular carcinoma

Abstract: Liver cancer occurs very frequently worldwide and hepatocellular carcinoma (HCC) accounts for more than 80% of total primary liver cancer cases. In this study, the anticarcinogenic effects of resveratrol against hepatitis B virus (HBV)-induced HCC were investigated by using HBV X-protein-overexpressing Huh7 (Huh7-HBx) human hepatoma cells. MTT assay showed that resveratrol decreased cell viability. Fluorescence-activated cell-sorter analysis showed that resveratrol induced G1 cell cycle arrest without increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…For example, resveratrol and piceid have similar antioxidant capacity, but piceid appears to be more efficacious than resveratrol due to its reaction with its radical form [ 22 , 23 ]. Indeed, resveratrol-glycoside was more effective than resveratrol against hepatitis B virus [ 24 , 25 ]. Piceatannol, with one more hydroxyl group, was already reported as having stronger anti-inflammatory, immunomodulatory, anti-proliferative, anti-leishmanial, anti-leukemic, and protein-tyrosine kinase inhibitory effects [ 19 ].…”
Section: Chemistry Of Resveratrolmentioning
confidence: 99%
“…For example, resveratrol and piceid have similar antioxidant capacity, but piceid appears to be more efficacious than resveratrol due to its reaction with its radical form [ 22 , 23 ]. Indeed, resveratrol-glycoside was more effective than resveratrol against hepatitis B virus [ 24 , 25 ]. Piceatannol, with one more hydroxyl group, was already reported as having stronger anti-inflammatory, immunomodulatory, anti-proliferative, anti-leishmanial, anti-leukemic, and protein-tyrosine kinase inhibitory effects [ 19 ].…”
Section: Chemistry Of Resveratrolmentioning
confidence: 99%
“…Lin et al ( 78 ) reported that resveratrol can promote the recovery of the fatty liver and effectively decrease the incidence of HCC caused by the HBV X protein (HBX) in HBX transgenic mice via downregulating lipogenesis, promoting transient liver regeneration and stimulating antioxidant activity. Additionally, it has been demonstrated that resveratrol has therapeutic effects on HCC through the p53 ( 84 ), cell cycle ( 85 87 ). A previous study revealed that menadione kills tumor cells by influencing their redox cycle ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds derived from animals, microorganism, and in particular from plants have been used and have demonstrated significant efficacy in the prevention and treatment of various human disease, including cancer. Various studies have demonstrated that the combination of chemotherapeutic agents and resveratrol (RV), a polyphenol found in red wine with antioxidant, anti-inflammatory [ 55 ], cardioprotective [ 56 ], and anticancer activities [ 57 , 58 ], lead to the inhibition of tumor growth and enhanced antitumor effect compared to chemotherapy alone [ 59 ]. Recently, in vitro and in vivo studies have reported the effects of RV in NB proliferation and progression.…”
Section: Nutraceutical Compounds and Nbmentioning
confidence: 99%